A Production systems study of Easy Call Communications Philippines, Inc. - Borjal, June U. (College of Engineering, 1995)
The study is about EasyCall Front Office in Galleria. EasyCall is engaged in the provision of a range of radio common carrier paging and message handling services. The Front Office is where various transactions such as billing, new sale, servicing, and others are made. This study aims to arrive at an optimum level of system utilization through determining the maximum number of servers, develop strategies that would lessen waiting times so as to avoid long queues. The study also deals with the development of simulation models to describe the actual situation, particularly the arrival and departure of customers. Data were gathered through interviews, survey time study, and direct observation.From these, critical analyses were drawn using queuing models, simulation and with the aid of statistical tables and flowcharts. Given the aspiration level or maximum waiting time of fifteen (15) minutes, the company is working at the optimum level. That is, four (4) servers having a service rate of 8.14 customers per hour. This however, is not an optimum level in the customers point of view. The customer has an aspiration level or desired waiting time of less than five(5) minutes. If taken into consideration, this would require six FOPs. The current status of the system has an idle time of 41.67% in the morning and none during peak hours. Thus an FOP of six would only be fully utilized during peak hours but would be idle for the rest of the day. The group presented several recommendations to be taken into account by the company.